Relationship between Self-efficacy and self regulated with procrastination: Compare students with learning disabilities and normal - Zahra Naghsh; Zahra Ramezani khamsi (پژوهش‌های کاربردی روانشناختی, 2018)
The purpose of this study was to investigate the relationship between self-regulated, self-efficacy with  procrastination, and compare disabilities students and normal students in structural model of this relationship. For this reason 300 students (150 disabilities students, 150 normal students) were chosen randomly (2, 6, 13, 18) and completed a questionnaire with 3 sub scales self-efficacy (Middelton, Midgly, 1997) self-regulation of Miller et al (1996), and procrastination of  Solomon and Ratblvm (1984). The results indicated that  there is difference between  disabilities students and normal students in structural model and both of them are not parallel and Training courses to enhance students' self-efficacy and self-regulated with learning disabilities to reduce their procrastination is usefull.